Analisis Variabel Yang Memengaruhi Pertumbuhan Dan Peningkatan Daya Saing Industri Amplang Samarinda - Isharyani, Muriani Emelda; Ananta, Muhammad Yuda; Kuncoro, Deasy Kartika Rahayu (Jurnal Teknik Industri, 2014)
Several problems occurred in amplang industry of Samarinda insists on discovering indicators and factors affecting the growth and improvement of amplang industry’s competitiveness of Samarinda. Identification and analysis are done by using Structural Equation Modelling (SEM) method toward indicators and factors of Diamond Porter model. The results of this research indicates that all indicators that compose and build each factor of Diamond Porter model literally have a positive and significant correlation to each factor. Each indicator evidently influences positively and significantly on the growth and improvement of amplang industry’s competitiveness of Samarinda. Moreover, factors of Diamond Porter model positively and significantly evidently influence to the growth and improvement of amplang industry’s competitiveness of Samarinda. Based on the influential factors and indicators, it can be identified that condition & resource and capital resource availability are the most influential factor and indicator on the growth and improvement of amplang industry’s competitiveness of Samarinda.